From ''being to the self'' to ''become to be'': on development of autonomy construction in nursing students - Roberta Waterkemper; Marta Lenise do Prado; José Luis Medina-Moya; Vânia Marli Schubert Backes (Universidad de Antioquia, 2014)
Objective. To understand nursing student's self-consciousness and his/her autonomy in the discipline of fundamentals of professional care in the context of a liberating pedagogical proposal. Methodology. This qualitative, case-based research in the model of Ludke and André involved 14 students participating in the discipline. Data were collected by non-participatory observation and analysis of documents. Field observation was conducted from March to July 2010 and data were collected according to the proposal of Minayo: pre-analysis, exploration of material and treatment of results. Results. We constructed two thematic units of analysis: from ''being to the self'' and exercise of ''become to be''. Conclusion. When nursing students feel more liberty, they have the opportunity to substitute the scary prospect of learning something new material to something that motivates their curiosity and leads them to become more autonomous.